Residue number system for two-dimensional discrete wavelet transform - Tay, Thian Fatt. (2011)
Discrete wavelet transform (DWT) is the core image processing method used in JPEG 2000 Coding System. Currently, there are many DWT processing unit designed in Binary Number system. This project involves designing the first two-dimensional lifting-based DWT architecture in Residue Number System (RNS). The main purpose of designing this processing unit in RNS is due to its inherent properties such as modularity, parallelism and carry-free computation which enable faster computation speed. This report discusses the advantages of residue arithmetic, JPEG2000 Coding System, the implementation of the proposed RNS floating point arithmetic unit, design flow of proposed RNS 2-D Lifting-based DWT architecture, from RTL coding to synthesis of the design, and modelling of the proposed architecture using Matlab.